Molecular Detection and Genotyping of Enterocytozoon bieneusi in Pigs in Shanxi Province, North China - Zhang, Zhen-Huan; Qin, Rui-Lin; Liu, Ya-Ya; Zou, Yang; Mei, Jin-Jin; Liu, Qing; Gao, Wen-Wei; Zhu, Xing-Quan; Ren, Yu-Hong; Xie, Shi-Chen (Frontiers in Veterinary Science, 2022)
Enterocytozoon bieneusi is a common opportunistic intestinal pathogen that can cause acute diarrhea in immunosuppressed humans and animals. Though E. bieneusi has been widely detected in pigs in the world, little is known of its prevalence and genotype distribution in pigs in Shanxi province, north China. In this study, a total of 362 fecal samples were collected from pigs in three representative counties in north, south and central Shanxi province, China. The prevalence and genotypes of E. bieneusi were investigated by nested PCR amplification of the ribosomal internal transcribed spacer (ITS) region of the rRNA gene. Overall, the prevalence of E. bieneusi in pigs in Shanxi province was 54.70% (198/362). Statistical analysis showed the difference in prevalence was statistically significant between regions (χ2=41.94, df=2, P <0.001) and ages (χ2=80.37, df=1, P <0.001). In addition, 16 genotypes of E. bieneusi were identified in this study by sequence analysis of the ITS region, including 15 known genotypes (EbpC, EbpA, EbpB, pigEb4, PigEBITS5, I, Henan-Ⅰ, G, WildBoar 7, SH10, EbpD, CHC5, PigSpEb1, PigSpEb2 and CHG19) and one novel genotype (designated as PigSX-1). Phylogenetic analysis revealed that 14 known genotypes and the novel genotype were clustered into Group 1, whereas genotype I belonged to Group 2. To the best of our knowledge, this is the first report of the prevalence and genotypes of E. bieneusi in pigs in Shanxi province. These findings enrich the genetic diversity of E. bieneusi and provide the baseline data for the prevention and control of E. bieneusi in pigs in the study regions.